Family Participation in Learning Sundanese at Mi Mq An-Nuur - Hilda Rahmawati; Endah Robiatul Adawiyah; Linda Dwi Nurmasyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sundanese is the first language of the people of West Java, especially Subang district, but not a few people use Indonesian in various aspects of life, one of which is in education. Nowadays it is often found that children both at home and at their schools speak Indonesian as their daily language. Meanwhile, they forget the use of Sundanese which is their mother tongue, as well as when children at school in teaching Sundanese they often use Indonesian which is considered to interfere with the meaning, purpose and function of learning Sundanese. Therefore it is very important for researchers to conduct research with the aim of finding out why and what are the reasons for using Indonesian in their daily lives and finding out the role of families in using Sundanese in their lives so that their mother tongue is not forgotten and the goals to be achieved in research This is to find out how big the students at Mi Mq an-nuur are in using the national language and mother tongue, namely Sundanese. The method used in this study uses a qualitative approach through the ethnographic method. From the results of the study, the authors found that 65% of students when in their family environment used the National Language to communicate with their families, and the remaining 45% of students always used their mother tongue or Sundanese.